Metabolic optimization of the basketball jump-shot - Padulo, J.; Ular, D.; Vando, S.; Galasso, M.; Lo Storto, D.; Nikolaidis, P.; Ardigo, L. P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Due to its mixed physical-technical-tactical nature, basketball like other team sports needs attention on likely relationships between all its facets, e.g., metabolic power and technical skill. A common fundamental is the Jump-Shoot (JS), which can be shot both when just come off the bench and when fatigued by previous actions. Our aim was to study the effect of different metabolic power conditions on successful JS percentage (JS%). Methods: 22 male (Under 17) basketball players (age 15.7±0.9 y, height 179±6.9 cm, mass: 66.4±9.2 kg, sport experience 7.9±1.0 yrs). The participants threw JSs under three randomized testing sessions one week later than a Yo-Yo Intermittent Recovery test level 1 (Yo-Yo IR1) (Castagna et al, 2008) administered to measure HRMAX as a proxy of maximal metabolic power. All sessions consisted in 10 consecutive JSs from five different significant field spots 5-m far from the basket (two counter clockwise "laps") at different heart rates (HR): rest (0HR), after warm-up (HR at 50%HRMAX [50HR], 80%HRMAX [80HR]). The same procedure was repeated one week later to evaluate measures reliability. After a 15` standard warm-up running each participants threw 10 consecutive JSs sessions at different HRs (0HR - 50HR - 80HR). Each HR (continuously monitored with Cardio-SuuntoTM) was achieved by low/high intensity shuttle running (15+15 m). Reliability of the shoot accuracy measure at 0HR, 50HR and 80HR was assessed by Intra-class Correlations Coefficient (ICC) according to a previous study (Padulo et al, 2015). A one-way ANOVA within subjects was performed to check for the differences between the three sessions with post-hoc LSD test. The level of statistical significance was set at p<0.05. Results: ICC showed a good reliability at 0HR (0.89), 50HR (0.92) and 80HR (0.95). Yo-Yo IR1 HRMAX was 195.6±6.1 bpm. ANOVA showed difference in JS% over sessions (F(1.20)=4.257 and p=0.018) with 660 JSs. LSD test did not show any significant 0HR-50HR JS% difference (-9% and p>0.05), while 80HR elicited significantly lower values with respect to both 0HR and 50HR (-41 and -28% with p=0.006 and p<0.05, respectively). Discussion: Our study provided two practical indications to keep high JS%: 1) preliminary warm-up does not improve JS%, because the 0HR-50HR difference was not significant; and 2) 80HR decreases JS% significantly, providing therefore scientific support to the usual behavior by players, who aim always at resting as much as possible between game-play pauses.